Complete mitochondrial genome of the hybrid grouper Epinephelus lanceolatus (♀) × E. moara (♂). Issue 2 (3rd July 2018) - Park, Jong Yeon; Yoon, Ji Hun; Noh, Choong Hwan; Kang, Min Joo; Bang, In-Chul
Abstract: The complete mitochondrial genome of the novel hybrid grouper ( Epinephelus lanceolatus ♀ and E . moara ♂ ) includes 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNA genes, and 1 control region (D-loop), for a total length of 16, 743 bp. The overall nucleotide compositions encoded on the heavy strand are 29.73% A, 28.84% C, 15.08% G, and 26.64% T.